Diagnostični postopki pri raku endometrija - Takač, Iztok (Medicinski razgledi, 2001)
The most frequent sign od endometrial cancer is postmenopausal bleeding. In the early cancer stages, some women show no symptoms of the disease. Clinical examination reveals especially advanced forms of cancer while early forms are revealed by hysteroscopy and curettage, which is still golden standard for diagnosing this disease. Ultrasound allows a fairly reliable evaluation of the affection of the uterine wall and the spread of malignant tissue in the abdominal cavity. The same is true for computer tomography and nuclear magnetic resonance. Tumor markers are not specific of endometrial cancer. Steroid hormone receptors are significant guides in planning of treatment and predicting the course of disease. The latter also depends on the DNA content in cancer cells. The part played by oncogens in endometrial cancer is not yet clarified. Immunohistochemical methods are a mean of defining some rare endometrial malignomas.
Keywords: Endometrial neoplasms; Endometrijske novotvorbe; ginekologija; Diagnosis; Diagnostika; endometrij; rak (medicina)